Ovarian follicular waves in ovulation induction in assisted reproduction techniques (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: A greater understanding of the menstrual cycle and multiple waves of antral ovarian follicular development has challenged traditional concepts of female reproductive physiology and the foundations of assisted reproductive technologies (ART). Approximately two-thirds of women develop two follicle waves throughout an interovulatory interval, and the remainder exhibit three waves of follicle development. Major and minor waves of follicle development have been observed. Major waves are those in which a dominant follicle develops; dominant follicles either regress or ovulate. In minor waves, the physiological selection of a dominant follicle is not manifested. Knowledge of the waves of antral follicular development has led to the global adoption of novel ovarian stimulation strategies in which stimulation can be initiated at various times throughout the cycle. Random-start and luteal-phase ovarian stimulation regimens have important clinical applications in women requiring urgent oocyte or embryo cryopreservation for fertility preservation before chemotherapy.Objective:  To evaluate the role of multiple waves of the antral ovarian follicular in the menstrual cycle in ovulation induction in ART.Methods: A literature search using the keywords “multiple waves of antral ovarian follicular development,  In Vitro Fertilization, Ovarian stimulation ” was performed in the PubMed database.Outcome: Random start and luteal phase of ovulation induction in ART offer the same results in fertilization and pregnancy rates as conventional early follicular phase start.Conclusion: The primary benefits of the random-start protocol include a patient-oriented approach to care, timely and efficient treatment, and a lower dropout rate.  Women with poor ovarian reserve and those diagnosed with cancer will have a greater chance of successful assisted reproduction with the use of these strategies.